Teacher readiness in assessing students for Malay language writing: an exploratory study - Said, Rozita Radhiah; Jusoh, Zuraini; Md. Sabil, Azhar; Othman, Shamsudin (Universiti Putra Malaysia Press, 2021)
This study explores the knowledge, understanding, and mastery of writing skills assessment among Malay language secondary school teachers in Malaysia. A total of 182 respondents from 91 secondary schools from seven different zones in Malaysia were selected using a purposive sampling technique. Survey design with a five-point Likert scale questionnaire instrument used in the study consisted of 117 items related to writing skills assessment. Statistical analysis is explained using standard deviation and mean score. The results of the study indicated that the determinants of the mastery level of writing skills assessment recorded the highest mean (M=3.92, SD=0.494). Then, it is followed by the second construct, which involves the implementation aspects of the evaluation was also rated highly (M=3.91, SD=0.482). The results also showed a significant and positive relationship between all respondents’ knowledge and their understanding of writing assessment implementation and their mastery of writing skills assessment. The findings showed that the role of teachers as school-based appraisers is established and consistent with the guidelines outlined by the Ministry of Education Malaysia. Future research focusing on the implementation of writing skill assessment is suggested to ensure that the evaluation done is systematic and reliable.